Effects of extraction conditions on yield, total phenolic contents and antibacterial activity of methanolic Cinnamomum zeylanicum Blume leaves extract - Yusoff, Ida Madiha; Rukayadi, Yaya; Hussain, Norhayati (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2017)
Increase of foodborne diseases has promulgated the development of new natural food additive with high extraction yield to eliminate food pathogenic organisms. One such possibility is the use of plant product as antibacterial agents with non-conventional method to enhance the yield. In this study, cinnamon leaves (Cinnamomum zeylanicum Blume) were subjected to ultrasonic assisted extraction (UAE) using response surface methodology (RSM) to optimise extraction yield and total phenolic contents. The effect of two independent factors, extraction temperature (x1: 25-40°C) and extraction time (x2: 15-45 minutes) were investigated. Optimum extraction yield and total phenolic contents of cinnamon leaves were 27.49 ± 1.59% and 3987 ± 79.10 mg GAE/g which were closely as predicted using RSM (28.34%, 4048 mg GAE/g), respectively. The optimum condition of extraction yield (40°C and 45 minutes) showed the maximum zone of inhibition against all tested foodborne pathogens (7.33 ± 0.50 to 13.22 ± 0.44 mm), whereas optimum condition of total phenolic contents (33°C and 31 minutes) showed the lowest zone inhibition (6.78 ± 0.67 mm to 11.67 ± 1.41 mm). The minimal inhibitory concentration (MIC) values range from 97.65 to 6250.00 μg/mL and minimal bactericidal concentration (MBC) values from 6.25 to 50.00 mg/mL. These results indicated that UAE method is excellent in producing significantly the highest of extraction yield, total phenolic contents and act as a potential natural antibacterial agent even using low extraction temperature and short time.